2019
DOI: 10.1093/jacamr/dlz060
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial stewardship in South Africa: a scoping review of the published literature

Abstract: Objectives To map published data of antimicrobial stewardship (AMS) interventions that are currently being carried out in hospitals and clinics in the public and private health sectors of South Africa in line with the antimicrobial resistance (AMR) strategy of South Africa. Methods A systematic scoping review was conducted to identify AMS initiatives in the public and private health sectors of South Africa for the period 1 Ja… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 51 publications
0
32
0
Order By: Relevance
“…‘Antimicrobial Stewardship’ scored the lowest of all the AMR categories, suggesting that by focussing on this, real gains can be made in the fight against AMR. Whilst the introduction of antimicrobial stewardship has proved successful in some countries, and can be used as a template for others [ 34 , 35 ], this study has shown that most countries still need to create and implement national guidelines on the appropriate distribution and use of antimicrobials in a One Health capacity to limit the risk of resistance transmission [ 14 ]. Increased national awareness of AMR and the legislated use of antimicrobials is required, and professional bodies should be instigated to regulate and educate the pharmaceutical practices of both human and animal healthcare professionals.…”
Section: Discussionmentioning
confidence: 99%
“…‘Antimicrobial Stewardship’ scored the lowest of all the AMR categories, suggesting that by focussing on this, real gains can be made in the fight against AMR. Whilst the introduction of antimicrobial stewardship has proved successful in some countries, and can be used as a template for others [ 34 , 35 ], this study has shown that most countries still need to create and implement national guidelines on the appropriate distribution and use of antimicrobials in a One Health capacity to limit the risk of resistance transmission [ 14 ]. Increased national awareness of AMR and the legislated use of antimicrobials is required, and professional bodies should be instigated to regulate and educate the pharmaceutical practices of both human and animal healthcare professionals.…”
Section: Discussionmentioning
confidence: 99%
“…However, improved policing of these guidelines will be necessary to slow the development of AMR. A scoping review of published literature on antimicrobial stewardship (AMS) in South Africa suggested that AMS interventions should be addressed using a number of strategies: (i) prescription audits and usage; (ii) education and its impact; and (iii) the role of different healthcare professionals in AMS ( Chetty et al, 2019 ). The report concluded that there is value for AMS in both the public and private health sectors of South Africa and that initiatives are being carried out across both sectors but more attention needs to be focused on AMS implementation in line with the National AMR Strategy of South Africa.…”
Section: Discussionmentioning
confidence: 99%
“…The report concluded that there is value for AMS in both the public and private health sectors of South Africa and that initiatives are being carried out across both sectors but more attention needs to be focused on AMS implementation in line with the National AMR Strategy of South Africa. The authors report that collaboration between the different sectors will aid in overcoming the AMR challenge ( Chetty et al, 2019 ). An Australian study of companion animal, equine, and bovine veterinarians reported that veterinary practices rarely had antimicrobial prescribing policies ( Hardefeldt et al, 2018a ).…”
Section: Discussionmentioning
confidence: 99%
“…In the public sector, however, AMS implementations were only successfully accomplished in a few hospitals. 10,11,12,13 The results of a recent situational analysis of AMS activities in the KwaZulu-Natal (KZN) public sector hospital facilities paints a similar picture ('unpublished data'). Although a vast majority of hospitals had set up governance structures, including AMS committees and a term of reference, individual stewardship programmes were at different levels of functioning.…”
mentioning
confidence: 87%
“…14,16 Few examples of fully fledged ASPs are present in the public sector and success of these ASPs can be directly attributable to a multidisciplinary team and dedicated time and resources. 10,11,12,13 In the private sector, ASPs are more widespread and run across hospital groups. 17 Regardless of the sector, if interventions are accompanied with education and ongoing audits, ASPs would be successful and sustainable.…”
Section: Read Onlinementioning
confidence: 99%